The Unique Temporal System in Austronesian Languages: Tenselessness, Aspect, and Temporal Reference in Indonesian - Nurasia Natsir; Aisyah Aulia Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Unlike Indo-European languages, Indonesian (Bahasa Indonesia) and most other Austronesian languages lack grammatical tense marking, presenting a fundamental typological difference with significant implications for linguistic theory and second language acquisition. This study investigates how Indonesian expresses temporal reference without grammatical tense, comparing it with tensed languages, and exploring the cognitive and typological implications of tenselessness. We employed a mixed-methods approach combining: corpus analysis of 5,000 Indonesian sentences; comparative linguistic analysis with English and Mandarin Chinese; psycholinguistic experiments with 200 native Indonesian speakers; and a cross-linguistic survey of 15 Austronesian languages. Results revealed that Indonesian expresses temporality primarily through lexical temporal markers (sudah, sedang, akan) in 68.3% of contexts, temporal adverbials (82.1%), and contextual inference (34.5%). Psycholinguistic experiments showed no processing disadvantage for Indonesian speakers in temporal reasoning tasks compared to English speakers. Cross-linguistic analysis confirmed that 86.7% of surveyed Austronesian languages lack grammatical tense, suggesting tenselessness represents a stable inherited feature of the family. Indonesian's tenseless system represents not a linguistic deficit but an alternative, equally sophisticated means of temporal expression. These findings challenge universal claims about tense as a necessary grammatical category and have significant implications for linguistictypology, second language pedagogy, and theories of universal grammar.